THE EFFECT OF VACCINATION IN CONTROLING BACTERIAL DISEASE CAUSED BY AEROMONAS HYDROPHILA IN NILE TILAPIA (OREOCHROMIS NILOTICUS) - Ratulangi, Arne A; Tumbol, Reiny; Manoppo, Hengky; Pangkey, Henneke (AQUATIC SCIENCE & MANAGEMENT, 2014)
This study aims to apply vaccination against bacterial disease. The purpose of vaccination is to trigger the immune respone both non-specific and specific of fish against bacteria Motile Aeromonas Septicaemia (MAS) caused by Aeromonas hydrophila. The vaccination for fish with different ages: 2-3 weeks and 5 weeks were done using immersion method. The fish were re-vaccinated (booster) after two weeks of the first vaccination. The survival rate was < 50 % for juveniles 2-3 weeks and > 50% for juveniles 5 weeks. Survival rate for juveniles 5 weeks was higher than juveniles of 2-3 weeks. This shows that organs of juveniles of 5 weeks were more complete than the 2-3 weeks juveniles. The age of fish is one of the important factors for successfully vaccination. Penelitian ini bertujuan untuk melakukan penerapan vaksinasi terhadap penyakit bakterial. Vaksinasi ditujukan untuk merangsang respon kekebalan non- spesifik dan spesifik pada tubuh ikan terhadap penyakit Motile Aeromonas Septicaemia (MAS) yang disebabkan oleh bakteri Aeromonas hydrophila. Vaksin diberikan pada benih ikan nila yang berbeda umur yaitu 2-3 minggu dan 5 minggu dengan menggunakan metode perendaman. Ikan divaksinasi ulang (booster) setelah 2 (dua) minggu dari vaksinasi yang pertama. Prosentase kelangsungan hidup < 50 % untuk benih umur 2-3 minggu dan > 50% untuk benih umur 5 minggu. Jumlah kematian benih umur 2-3 minggu lebih tinggi dari 5 minggu. Hal ini menunjukkan bahwa fungsi organ benih umur 5 minggu telah lebih lengkap dari pada benih umur 2-3 minggu. Umur ikan merupakan salah satu faktor penting penentu keberhasilan suatu kegiatan vaksinasi.